Efficacy of Entrepreneurs' Psychological Capital on the Performance of New Ventures in the Development of Regional Economy in the Greater Bay Area - Chen, Hongbo; Tao, Yitao (Frontiers in Psychology, 2021)
The study aims to analyze the relationship between the psychological capital and enterprise performance of the entrepreneurs and provide direction for the optimization of regional economic development and talent introduction mechanism. First, the theoretical basis is established from regional economic development, innovative talent introduction, and individual psychological capital theory, according to which the questionnaire survey is designed, and four dimensions of self-efficacy (C), wish (W), toughness (T), and optimism (O) are selected to set the questions on psychological capital and innovation performance. Then, following statistical analysis, the characteristics of the new ventures are revealed. Finally, based on the empirical research model, the hypotheses are put forward based on psychological capital and its four subdimensions, and the relationship between the efficacy of the psychological capital and the performance of new ventures of the entrepreneurs is revealed through regression analysis. The results show that the proportion of the computer and education industry in the new ventures reaches 67.7%, and the proportion of enterprises with 1–5 entrepreneurial years reaches 78%. Meanwhile, the proportion of first-time entrepreneurship is 60.5%, and the proportion of entrepreneurs motivated by their ideal reaches 35.8%. The new entrepreneurs have a good grasp of the market situation, and the overall operation condition is stable. Most of them originate from micro and small enterprises (MSE). Psychological capital has a great influence on individual entrepreneurship. The empirical results show that the psychological capital of entrepreneurs has a positive effect on the performance of new ventures. Except for the subdimension of O, the other three subdimensions (C, T, and W) of psychological capital have a positive effect on the performance of new ventures, and psychological capital as a whole has the greatest impact. The results provide a reference for the relationship between the performance improvement of new ventures and regional economic development.